Nilai-nilai Sejarah Ilmu al-Qur’an dalam Naskah Kitab al-Mukarrar Karya Abi Hafish Umar bin Muhammad al-Mishri; Koleksi Gus Mahin Pengasuh Pondok Pesantren Al-Yasir Kauman Jekulo Kudus - Nugroho, Muhammad Agustian Andi; Azizah, Laili Noor (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2022)
Historical Values of Qur'anic Science in the Book of al-Mukarrar Manuscript by Abi Hafish Umar bin Muhammad al-Mishri; Collection of Gus Mahin Teacher of al-Yasir Kauman Islamic Boarding School Jekulo Kudus. This research examines the science of the al-Qur’an contained in manuscript al-Mukarrar three things: 1) How is the history the manuscript of Al-Mukarrar?, 2) How is the descripton of the manuscript of Al-Mukarrar, 3) What historical value can be taken from the Al-Mukarrar manuscript? This research uses a philological procedure with interpretive analysis to reveal history and some values that can be taken from book Al-Mukarrar. The conclusion from the research shows that the tradition of writing in the period of the ulama’ in ancient times was not only related to the inner expression (qalb), but also as a response to the importance of knowledge about the procedures for reading the Qur’an according to seven different Qira’at priests, explaining the knowledge of the tajwid and its benefit as well as about monotheism. It can be seen that this book has historical value including: (1) As evidence of the existence of a book that discusses the Science of the Qur’an. (2) As an addition to library literacy. (3) As a source of knowledge. Especially the value of the three in the study of the sience of the Qur’an.